FOOD AND BEVERAGE PURCHASING DECISIONS IN THE MALANG MSME SECTOR ARE INFLUENCED BY THE HALAL LABEL AND PRODUCT QUALITY - NADLIROH, INDAH DATIN; PUJI HANDAYATI; ARIEF NOVIARAKHMAN ZAGLADI (Akademika : Jurnal Manajemen, Akuntansi, dan Bisnis., 2024)
The most significant economic pillars supporting Indonesia's development and growth are Micro, Small, and Medium-Sized Enterprises (MSMEs), particularly in the Malang region. In recent years, Malang's MSMEs business sector has grown significantly. Meeting the rising needs of consumers is essential for MSME firms to succeed. In this situation, it's critical for MSMEs to secure halal certification for their goods and goods with quality assurance. The goals of this study are to: (1) ascertain the impact of halal labels on consumer decisions regarding food and beverage products in the Malang MSME sector; (2) ascertain the impact of product quality on consumer decisions concerning food and beverage products in the Malang MSME sector; and (3) ascertain the impact of both halal labels and product quality at the same time. The sample in this study consists of 70 individuals, with the population in this study including all customers who buy and consume halal-certified MSME food and beverage goods in Malang. Multiple linear regression analysis is the data analysis technique employed in this study. The study's findings indicate that the product quality variable has a tcount of 1.107 and a significance level of 0.272 above 0.05, whereas the halal label variable has a tcount of -0.251 and a significance level of 0.803 above 0.05.